2022
DOI: 10.1093/ehjcr/ytac333
|View full text |Cite
|
Sign up to set email alerts
|

Coronary physiology to guide treatment of coronary artery disease in a patient with severe aortic valve stenosis: friend or foe? A case report

Abstract: Background Severe aortic valve stenosis (AS) is the most frequent valve pathology in the developed world requiring intervention. Due to common factors in pathogenesis, patients with AS frequently have concomitant coronary artery disease (CAD). Determining the relative contribution of each component to the disease state is not easy as there is much overlap in complaints. Moreover, severe AS interferes with the haemodynamic assessment of intermediate coronary lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“… 26 Due to many physiological changes, it is advised to be careful about the interpretation of the different indices in this population until enough data are available. 8 , 9 The study of coronary physiology in the population with severe AS is therefore very important and could clarify the uncertainty that currently still exists in clinical practice. 3 , 27 Studies regarding this topic have very different sample sizes and have provided us with conflicting individual results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Due to many physiological changes, it is advised to be careful about the interpretation of the different indices in this population until enough data are available. 8 , 9 The study of coronary physiology in the population with severe AS is therefore very important and could clarify the uncertainty that currently still exists in clinical practice. 3 , 27 Studies regarding this topic have very different sample sizes and have provided us with conflicting individual results.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The question remains whether the currently used and validated cut‐offs in the non‐AS population can confidently be translated to and be used in patients with severe AS. 9 Several studies have tried to study the short‐ and long‐term changes in commonly used pressure indices after TAVR. Most individual studies were small and showed sometimes conflicting results.…”
mentioning
confidence: 99%
“…Using coronary physiology to guide revascularization in TAVI patients can be challenging since there are multiple complicated physiological changes at play. 3 Recently, a small study has suggested that fractional flow reserve remains more stable when compared with resting full-cycle ratio after TAVI; however, more research is needed to confirm this. 4,5 In our opinion, it might have been better not to include the patients who underwent physiology-guided PCI or to analyze them as a separate group.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Studies report stable or increased RFR values after TAVI, emphasizing that even the resting indices, can change due to a lower resting coronary flow after TAVI. 1 Moreover, in the VALIDATE-RFR study the sensitivity of both RFR and instantaneous wave-free ratio (iFR) were notably lower for the RCA. 5 Even though coronary perfusion is predominantly diastolic, the RCA perfuses in systole to a greater degree than the left coronary system, probably due to the thinner-walled right ventricle, which results in less systolic compression.…”
mentioning
confidence: 94%
“…We read with great enthusiasm the elegantly written case from Minten et al 1 regarding the use of coronary physiology for invasive functional assessment of coronary lesions in patients with severe aortic stenosis (AS). The authors measured the haemodynamic significance of a lesion in the mid-right coronary artery (RCA) in a patient with severe AS, by using fractional flow reserve (FFR) and the non-hyperaemic resting full-cycle ratio (RFR) before and after transcatheter aortic valve implantation (TAVI).…”
mentioning
confidence: 99%